Tecitura da identidade profissional da primeira turma do curso de graduação em Enfermagem da Universidade Federal de Alagoas: contribuição do corpo docente– 1973/1977 - Costa, Laís de Miranda Crispim (2012)
It is a socio-historical study that aimed to examine the contribution of the faculty to the formation of professional identity of the students of the first undergraduate degree in nursing from Alagoas and discuss the contributions of this faculty to the nursing in Alagoas. The clipping was the social and temporal city of Maceió, in the period between 1973 and 1977, with the initial mark the official news of the course creation and as late mark the graduation of the first class in June 1977. The theoretical framework was the "Civilizing Process" of Norbert Elias. The primary sources were the official documents of the Central Archive of the Nursing Course Coordination Council and Federal University of Alagoas, the documents resulting from the transcription of the interviews of teachers and their personal files. Secondary sources were written by authors who discuss the history of Brazil and Alagoas. To collect the testimonials we used the Oral History theme through a semistructured interview. All subjects signed an informed consent and the project was approved by CEPE / UFAL (No. 23065.015735/2011-40 process). 13 people were interviewed and data analysis did understand that the rearrangement of teachers in the course contributed to the professional identity of students from the first group, mainly in three directions: the construction of identity "be a nurse" in the way of putting in services health and how to position themselves politically. Teachers provided a solid education so that the students build a professional identity of a competent nurse, with knowledge, skill and attitude, able to lead the nursing team and learn to stand before other health professionals with commitment and zeal for their chosen profession.